A quantitative and qualitative analysis of Time-Driven Activity Based Costing: the waste side of joint replacement - Fidanza, Andrea; Schettini, Irene; Di Petrillo, Francesco; Saracco, Michela; Petralia, Giuseppe; Logroscino, Giandomenico (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The Time-Driven Activity Based Costing (TDABC) is a recent and sophisticated analytical accounting systems capable of linking and summarizing the information held by the various stakeholders involved in the provision of health care services. The aim of this review is to quantify the current state of the art of the international TDACB literature in the orthopaedic field, highlighting which orthopaedic topic deriving from the clinical/economic interdisciplinarity is of greater interest. Methods: A comprehensive science mapping bibliometric analysis of scientific literature was performed using the Scopus database. Afterwards, the analysis of the 40 most cited articles was carried out to spotlight the area of greatest interest in the orthopaedic field, and from which to extrapolate a qualitative analysis. Results: A total of 346 documents resulted eligible for the review. Nine of 40 articles examined TDABC in the prosthetic context. Despite showing a high diversity of methodological application, all 9 articles agree on the two most expensive items of care cycles: operating room consumables followed by length of stay. Conclusion: TDABC is a cost calculation methodology that is gaining scientific attention in the orthopaedic world, particularly in the joint replacement area. This tool might be useful for both clinicians and business managers, allowing them to redesign the entire patient care path, making useful changes to reduce waste, while maintaining standards of care.